Strengthening Ecological Environment-Based P5 through Deep Learning Implementation in Elementary Schools - Nurandaryani; Hamna (Program Studi PGSD Universitas Madako Tolitoli, 2025)
Elementary school in Indonesia aims to cultivate a generation that excels academically while embodying Pancasila values and demonstrating environmental awareness. This study analyzes the implementation of a Deep Learning approach in strengthening the P5 framework through mindful, joyful, and meaningful learning in elementary schools, with the goal of fostering students’ environmental concern through practical school-based activities. The research employed a qualitative approach with a case study design at SD Negeri 2 Timoreng Panua, involving 48 informants, including the school principal, two teachers, and 45 students. The results indicate that the implementation of P5 reinforcement based on Deep Learning enhances students’ environmental awareness, measured through moral awareness (83.09%), learning enjoyment (83.53%), and learning significance that reinforces the values of mutual cooperation (81.50%), responsibility (78.05%), and tolerance (75.62%). The mindful, joyful, and meaningful learning approach successfully created a reflective learning ecosystem that is aligned with Pancasila values and environmentally friendly, while effectively promoting students’ critical thinking, empathy, and ecological consciousness. These findings underscore the importance of conscious, enjoyable, and meaningful learning strategies for strengthening Pancasila character and environmental stewardship in primary education.